PENDAMPINGAN UMKM “BAKPIA CRISPY 3 BINTANG” MELALUI PENGEMBANGAN PEMASARAN DAN LEGALITAS - Damayanti, Damayanti; Sari, Agustina Putri Kurnia; Nufus, Fadiela Rokhiliantien (Fokus ABDIMAS, 2023)
MSMEs that produce "Bakpia Crispy 3 Bintang" are located on Jl. Setiyabudi No.16 Kutoharjo Village, Rembang District, Rembang Regency has been established since 2009. The problems faced by partners are 1). The marketing is still not broad enough and tends to be passive, in this case the owner markets his product within the Rembang Regency, 2). Do not yet have a P-IRT (Household Industry Product) so that MSMEs cannot market their products to the fullest extent, and 3). Unattractive form of packaging. Community service programs carried out are 1). Expansion of marketing through the installation of banners, 2). Management of permits and business legality. The existence of a certificate from the Health Service for UMKM "Bakpia Crispy 3 Bintang" has a positive impact, because the community has recognized the legality of this UMKM and the public's trust has increased, 3). Making Instagram and Shopee social media accounts and making new packaging designs to make packaging more attractive and attractive to consumers.Keyword: Assistance, MSME, Marketing Development and Legality